1993
DOI: 10.3109/00498259309059451
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of benzoic acid with glycine in human liver and kidney: a study on the interindividual variability

Abstract: 1. The rate of conjugation of benzoic acid with glycine was measured in the homogenates of 110 specimens of human liver and in 67 specimens of human renal cortex. 2. The assay for the formation of benzoyl glycine consisted of measuring the formation of benzoyl glycine from (14C) benzoic acid and glycine in the presence of coenzyme A and ATP. 3. In human liver, the mean (+/- SD) and coefficient of variation for the formation rate of benzoyl glycine were 254 +/- 90.5 nmol min-1 per g liver and 36%, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…These metabolites can also be formed at other sites, such as the kidney. For example, in vitro studies support the conjugation of benzoic acid with glycine in human liver and kidney tissues (Caldwell et al, 1976;Temellini et al, 1993). Alternatively, a portion of the conjugates formed may be excreted into the intestinal lumen (via biliary excretion or exsorption) and excreted in feces.…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites can also be formed at other sites, such as the kidney. For example, in vitro studies support the conjugation of benzoic acid with glycine in human liver and kidney tissues (Caldwell et al, 1976;Temellini et al, 1993). Alternatively, a portion of the conjugates formed may be excreted into the intestinal lumen (via biliary excretion or exsorption) and excreted in feces.…”
Section: Discussionmentioning
confidence: 99%
“…Using human liver samples, it was demonstrated that there is interindividual variation in the capacity for hippurate synthesis from benzoate, ATP, CoASH, and glycine (Temellini et al, 1993). In another study it was found that some isovaleric acidemia patients do not respond very well to glycine supplementation therapy, even in South Africa, where all known patients are homozygous for the same disease-causing mutation (Dercksen et al, 2012).…”
Section: Factors That Influence Interindividual Variation In Glycine mentioning
confidence: 96%
“…The chemical shift regions of the spectra responsible for this separation of the data were from the TCA cycle intermediates taurine, dimethylglycine, creatinine, the glucose region, and hippurate. Studies have shown that citrate, taurine, hippurate, and trimethylamine-N-oxide have a high interindividual variation in control animals (4,11,20,23). The normal physiological levels of hippurate in the urine are known to be highly variable due to alterations in the gut microbial contents as a result of external factors such as stress or a change in diet (8,9).…”
Section: Discussionmentioning
confidence: 99%